Psychiatric symptoms and syndromes in sarcoidosis: a systematic review and meta-analysis - Frans, Andreas; Van Hoye, Griet; Van Meerbeeck, Xavier; Morrens, Manuel; Van Den Eede, Filip (Frontiers in Medicine, 2025)
IntroductionSarcoidosis is often associated with psychiatric symptoms and syndromes (PSS). This systematic review and meta-analysis aimed to summarize available literature on the prevalence of PSS in sarcoidosis, as well as their potential associations.MethodsA systematic search was conducted across PubMed, including case reports and studies that investigated PSS in sarcoidosis. A meta-analysis was performed on studies that assessed the association between sarcoidosis and PSS, using odds ratios (OR).ResultsWe included 43 studies and 53 cases on PSS in patients with sarcoidosis. The weighted average prevalence was 24.9% for depression, 28.7% for anxiety, 29.2% for neurocognitive symptoms, 54.4% for fatigue, 50.5% for excessive daytime sleepiness and 26.9% for sleep disturbances and insomnia, with the best available evidence for depression, anxiety and fatigue. The meta-analysis (n = 962) confirms that patients with sarcoidosis have a significant increased risk of developing PSS when compared with healthy controls (OR = 5.498, CI = 0.430–70.238, p < 0.001). Depressive symptoms and fatigue were most reported on and demonstrated the strongest associations as well (resp. OR = 4.855, z = 2.401, p=0.016 and OR = 20.231, z = 2.868, p = 0.004). Significant associations with anxiety and neurocognitive symptoms were also observed, although with less available evidence. Case reports reveal a diagnostic diversity not reflected in study populations, including psychosis and catatonia.ConclusionSarcoidosis is associated with a higher prevalence of PSS. Nonetheless research in this area remains limited. Systematic use of standardized psychiatric assessment tools is recommended.